Correction of Fanconi Anemia Type C Phenotypic Abnormalities Using a Clinically Suitable Retroviral Vector Infection Protocol - Brian W. Freie; Parmesh Dutt; D. Wade Clapp M.D. (Cell Transplantation, 1996)
Fanconi anemia (FA) is a complex autosomal recessive disease with hematologic manifestations characterized by a progressive hypoplastic anemia, hypersensitivity to clastogenic agents, and an increased incidence of acute myelogenous leukemia. The cDNA that corrects one of four FA complementation subtypes, named Fanconi anemia Type C (FAC) has recently been identified. We constructed a simplified recombinant retrovirus (vMFGFAC) encoding only the FAC cDNA, and tested its ability to correct the FAC defect in a lymphocytic cell line and primary mobilized blood progenitor cells. In addition, the gene transfer efficiency using a clinically applicable gene transfer protocol into normal primitive hematopoietic progenitor cells, high proliferating potential colony forming cells (HPP-CFC), derived from CD34+ purified cord blood cells was examined. The gene transfer efficiency was significantly enhanced when cells were transduced with supernatant while adherent to a 30/35 KD fragment of fibronectin, FN30/35, and was similar to efficiency obtained by coculture with retrovirus packaging cells. Transduction of an FAC deficient lymphoid cell line with vMFGFAC supernatant resulted in an enhanced cell viability, and G-CSF mobilized peripheral blood cells from an FAC-deficient patient transduced with the vMFGFAC virus demonstrated enhanced progenitor cell colony formation. These data indicate that the vMFGFAC virus allows functional complementation of FAC in lymphoblasts and primary hematopoietic progenitors, and that primitive cord blood hematopoietic stem/progenitor cells can be transduced at an efficiency comparable to protocols using cocultivation if adherent to FN 30/35 fragment.